Improved engineering specification design for road hump : a case study on residential streets in Shah Alam / Nor Izzah Zainuddin - Zainuddin, Nor Izzah (2013)
Speed hump or also known as road hump is designed to ensure safety for both drivers and pedestrian. The use of speed humps in residential streets is an efficient way of controlling speed ofvehicles. However, in Malaysia some ofthe dimensions designed by the local authorities had been implemented on an 'ad hoc' basis without any proper standards or guidelines (HPU, 2002). Although Highway Planning Unit (HPU) and Standards and Industrial Research Institute of Malaysia (SIRIM) have stipulated specific ranges of dimensions for the installation of speed humps, however no perfect and ideal guidelines were introduced and were not properly enforced by the local authorities. Therefore, with many styles and inconsistent designs of the speed humps a well-established empirical study has been implemented to develop optimal designs consistency models. In this study, the geometric design of the speed hump was related to 85th percentile speed and discomfort level. The speed data were carried out by using a laser gun meter detector to obtain the spot speed data at the selected speed hump location and vibration data collection were carried out using triaxial acceleration transducers connected to Racelogic VBOX II SX. Multiple linear regression analysis was conducted to develop a statistical relationship between speed hump geometric, 85th percentile speed and discomfort level. In the validation stage, the site empirical data were compared with the predicted data using the paired T -test and discrepancy measure such as Root Mean Squared Error (RMSE), Mean Absolute Error (MAE), and Mean Absolute Percentage Error (MAPE). Finally, the models have successfully developed and validated according to the statistical procedures in the study. The findings are hoped to provide a starting point towards the development of a standard for the speed humps in residential areas which will not only focus on the effectiveness but also considering the safety and discomfort level of the road users while travelling on the speed hump.